Awareness of the Need for Change: A Constructivist Grounded Theory of Medical Students' Understanding of Human Rights in Mental Health - Peter Macsorley; Sarah Gordon; Tracey Gardiner; Giles Newton-Howes (Harvard FXB Center for Health and Human Rights, 2023)
Traditionally, teaching in psychiatry has had a passing focus on human rights. Against this backdrop, the aim of this study was to construct a theory of the learning value of a service user-led human rights-focused teaching program for final-year medical students. We used descriptive qualitative analysis based on constructivist grounded theory to examine final-year medical students' understandings of human rights following a formal teaching program. The overarching theory that emerged focuses on an awareness of the need for change within student learning. This involves both a need for understanding the mental health care system and a need for self-reflection. These two processes appear to interact, promoting learning about the value of a human rights focus. While acknowledging the difficulties in securing such a change, students felt that doing so would be valuable to the practice of mental health. This service user-led human rights teaching program produced new awareness in medical students, both in terms of their understanding of their own biases and in terms of understanding the influence of systemic and structural elements of the psychiatric system on the protection of service users' human rights. Teaching human rights in psychiatry is likely to enrich their future self-reflective practice.